THE USE OF BLENDED LEARNING METHOD IN ENHACING STUDENTS’ LISTENING SKILL - Syamsuddin Syamsuddin; Andi Azis Jimi (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
This research aims at finding out whether Blended Learning method was able to improve the students’ achievement and motivation in learning Listening. This research used Action Research design. The subjects of the research were the third semester students of English Department, Faculty of Letters, University of Sawerigading Makassar. This research applied Classroom Action research which consisted of two cycles, each cycle comprised of planning, implementation, observation, and reflection. The data-collecting methods were observation and test. The data were analyzed using descriptive comparative manner. The result of the research revealed that learning listening through blended learning method could improve the students’ achievement. The average score of the initial achievement was 42.07, while at the first cycle was 61.59, and finally, at the second cycle was 68.11. In addition, learning listening through Blended Learning method also increased the students’ learning motivation.